Knowledge and frequency of use of sunscreen in medical students from a Peruvian university: Conocimientos y frecuencia de uso del protector solar en estudiantes de medicina de una universidad peruana - Yep, Luciana (2024)
Objective: Determine the level of knowledge and frequency of use of sunscreen in g medical students from a Peruvian university. Materials and methods: Cross-sectional analytical research in 302 students, of both genders and different study cycles. A virtual survey was applied. Results: High level of knowledge 56%; increased with the study cycle p=0,006. Use of sunscreen was 28,8%, higher in women with 34,5%, it was significantly associated with the level of knowledge p=0,001, but not with the study cycle p=0,065. Mixed skin type (55%) and skin phototype III (58,3%) prevailed. The reason  not to use sunscreen was the oily consistency. The question that had more correct  answer was ¿Is solar radiation the main cause of skin cancer?.The use of sunscreen was significantly related to phototype p= 0,005. Conclusions: In the medical students of a Peruvian university, the level of knowledge about the use of sunscreen was high in 56%, higher in women, it increases significantly with the study cycle and favors the use of sunscreen. 28,7% of medical students always used sunscreen. The factors associated with the use of sunscreen were: the female gender, phototype and the level of knowledge.